The devil in disguise deception, delusion, and fanaticism in the early English enlightenment - Knights, Mark (Oxford Univ. Press, 2011)
This study illuminates the impact of the two British revolutions of the seventeenth century and the shifts in religious, political, scientific, literary, economic, social, and moral culture that they brought about. The book does so through the fascinating story of one family and their locality: the Cowpers of Hertford. Their dramatic history contains a murder mystery, bigamy, a scandal novel, and a tyrannized wife, all set against a backdrop of violently competing local factions, rampant religious prejudice, and the last conviction of a witch in England.